Perlindungan Hukum terhadap Nasabah BTPN Jenius akibat Tindakan Phishing (Studi Kasus Bank Tabungan Pensiunan Nasional Jenius) - Yosefine Yosefine; Rani Sri Agustina; Dede Agus (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2023)
This article discusses phishing activities that have led to allegations of leakage of personal data from Jenius customers, which is one of the digital banking applications from the National Pension Savings Bank (BTPN). This phishing activity causes the loss of customer deposits in the Jenius application. Law Number 10 of 1998 concerning Banking and Law Number 19 of 2016 concerning Information and Electronic Transactions are used as references in this study. The purpose of this study is to identify and analyze legal protection for customers and to identify and analyze the legal responsibilities given by banks to customers. The research method used is normative juridical through legislation approach, conceptual approach, case approach and qualitative descrptive analysis. The source of the data used is secondary data in the form of library research and is supported by primary data obtained by interview. Based on the research results, the legal protection provided to customers is by applying the principle of confidentiality by banks as regulated in Law Number 10 of 1998 concerning Banking, although the Banking Law does not regulate in detail regarding digital banking. Phishing activities themselves have been regulated and threatened in Law Number 19 of 2016 concerning Information and Electronic Transactions. The responsibility given by the bank is to provide complaint services and carry out inspections/investigations as well as assist customers in finding solutions for losses suffered by customers